Behavior of thin-walled beam-column modular connection subject to bending load - Dhanapal, Jothiarun; Ghaednia, Hossein; Das, Sreekanta; Velocci, Jonathan (Thin-walled structures, 2020)
Steel modular construction has the potential to meet the growing infrastructure needs of the big cities and hence, the demand for modular construction is on the rise. This paper introduces a unique and innovative modular construction technique which involves the use of thin-walled hollow structural steel members and a state-of-the-art cast-steel connector, namely VectorBloc connector. The performance of the beam-column connections to be used in this modular construction largely determines its performance and success. In the present study, uniaxial and biaxial bending behavior of a typical corner beam-column connection made of thin-walled hollow structural steel members and VectorBloc connector was studied through full-scale tests and nonlinear finite element method. This beam-column connection will be used for constructing an assisted living facility. This study concludes that the design loads of the proposed assisted living facility can be safely carried by the VectorBloc connection. However, the weight of the VectorBloc connector can be reduced to 80% without compromising the design requirements of the assisted living facility. This study also concludes that the VectorBloc connection can be considered as a rigid connection. However, effective bracings against horizontal displacements must be provided in the structure in which the connection is intended to be used. •This paper presents a thin-walled modular connection using an innovative cast-steel connector.•This study shows that the proposed modular connection can safely carry the design bending loads.•This study shows the feasibility of reducing the connector weight to 80% of its present weight.•This paper highlights the possible use of the proposed modular connection as a rigid connection.•This paper presents an interaction diagram for use in the design of this modular connection.